Digital prediction technologies in the justice system: The implications of a 'race-neutral' agenda. (August 2020) - Ugwudike, Pamela
This article critically analyses the nexus of race and risk prediction technologies applied in justice systems across western jurisdictions. There is mounting evidence that the technologies are overpredicting the risk of recidivism posed by racialized groups, particularly black people. Yet the technologies are ostensibly race neutral in the sense that they do not refer explicitly to race. They are also compliant with race equality laws. To investigate how apparently race neutral technologies can nevertheless yield racially disparate outcomes, the article draws on insights distilled from the sociology of race and the sociological scholarship on standardization. It uses themes from these two scholarships to unravel the intersecting structural and creational dynamics capable of fomenting the digital racialization of risk.